The Promoting Effect of Gut Microbiota on Growth and Development of Red Palm Weevil, Rhynchophorus ferrugineus (Olivier) (Coleoptera: Dryophthoridae) by Modulating Its Nutritional Metabolism - Habineza, Prosper; Muhammad, Abrar; Ji, Tianliang; Xiao, Rong; Yin, Xianyuan; Hou, Youming; Shi, Zhanghong (Frontiers in Microbiology, 2019)
Red palm weevil (RPW), Rhynchophorus ferrugineus Olivier, is a destructive pest for palm trees worldwide. Recent studies have shown that RPW gut is colonized by microbes and alterations in gut microbiota can significantly modify its hemolymph nutrition content. However, the exact effects of gut microbiota on RPW phenotype and the underlying mechanisms remain elusive. Here germ-free (GF) RPW larvae were generated from dechorionated eggs which were reared on sterilized artificial food under axenic conditions. Compared with controls, the larval development of GF RPW individuals was markedly depressed and their body mass was reduced as well. Furthermore, the content of hemolymph protein, glucose and triglyceride were dropped significantly in GF RPW larvae. Interestingly, introducing gut microbiota into GF individuals could significantly increase the levels of the three nutrition indices. Additionally, it has also been demonstrated that RPW larvae monoassociated with Lactococcus lactis exhibited the same level of protein content with the CR (conventionally reared) insects while feeding Enterobacter cloacae to GF larvae increased their hemolymph triglyceride and glucose content markedly. Consequently, our findings suggest that gut microbiota profoundly affect the development of this pest by regulating its nutrition metabolism and different gut bacterial species show distinct impact on host physiology. Taken together, the establishment of GF and gnotobiotic RPW larvae will advance the elucidation of molecular mechanisms behind the interactions between RPW and its gut microbiota.